2017
DOI: 10.1210/en.2016-1658
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Mild Stress Causes Bone Loss via an Osteoblast-Specific Glucocorticoid-Dependent Mechanism

Abstract: Chronic stress and depression are associated with alterations in the hypothalamic-pituitary-adrenal signaling cascade and considered a risk factor for bone loss and fractures. However, the mechanisms underlying the association between stress and poor bone health are unclear. Using a transgenic (tg) mouse model in which glucocorticoid signaling is selectively disrupted in mature osteoblasts and osteocytes [11β-hydroxysteroid-dehydrogenase type 2 (HSD2)OB-tg mice], the present study examines the impact of chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 38 publications
3
17
0
Order By: Relevance
“…Overall, the increased glucocorticoid level may lead to negative bone turnover and subsequently bone loss. This mechanism explains the report of Henneicke et al, whereby even chronic mild stress upregulates glucocorticoid signalling, which subsequently causes bone loss, in a site-and gender-specific manner [14].…”
Section: Physiological Factorsmentioning
confidence: 55%
See 1 more Smart Citation
“…Overall, the increased glucocorticoid level may lead to negative bone turnover and subsequently bone loss. This mechanism explains the report of Henneicke et al, whereby even chronic mild stress upregulates glucocorticoid signalling, which subsequently causes bone loss, in a site-and gender-specific manner [14].…”
Section: Physiological Factorsmentioning
confidence: 55%
“…Several studies have demonstrated that psychological stress is associated with osteoporosis [12][13][14][15][16]. Fink et al demonstrated that the number of stressful life events correlated positively with the risk of concurrent accelerated hip bone loss in older men [15].…”
Section: Ivyspringmentioning
confidence: 99%
“…Meanwhile, prenatal caffeine exposure reduced the bone 11β‐HSD2 expression in male offspring before and after birth. Previous studies reported that the stable expression of 11β‐HSD2 in bone tissue can inactivate serum corticosterone and effectively regulate the bone corticosterone level to ensure the normal bone development (Henneicke et al, 2017; McNeil et al, 2007). So, these findings suggested that the continuously increased bone corticosterone was attributed to the reduced bone 11β‐HSD2 expression in prenatal caffeine exposure male offspring.…”
Section: Discussionmentioning
confidence: 99%
“…[ 251 ] The relationship between psychological stress and osteoporosis has been demonstrated with chronic mild stress, an established rodent model which leads to depression, causing reduction in osteoblast number, bone loss and reduced bone formation. [ 252,253 ] Peripheral nerves participate in regulating bone metabolism in individuals with psychological stress ( Figure A). One way in which psychological stress may impact osteoporotic disease risk and severity is through catecholamine‐induced activation of β ‐adrenergic receptors on osteoblasts and osteoclasts, which can increase RANKL expression and result in osteoclast differentiation.…”
Section: Crosstalk Between Bone and Intrabony Nerves In Pathophysiolomentioning
confidence: 99%